2021
DOI: 10.3389/fmolb.2021.737821
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Meta-Analytic Validation of RNA Sequencing Signatures for Predicting Status of Microsatellite Instability

Abstract: Microsatellite instability (MSI) is an important diagnostic and prognostic cancer biomarker. In colorectal, cervical, ovarian, and gastric cancers, it can guide the prescription of chemotherapy and immunotherapy. In laboratory diagnostics of susceptible tumors, MSI is routinely detected by the size of marker polymerase chain reaction products encompassing frequent microsatellite expansion regions. Alternatively, MSI status is screened indirectly by immunohistochemical interrogation of microsatellite binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The SETDB1 expression and HLA-related genes in ACC, CESC, and KIRC were positively correlated but were negatively correlated in other cancers in TCGA ( Figure 12(c) ). TMB and MSI are emerging predictors associated with survival and response to immunotherapy [ 30 , 31 ]. This study showed that SETDB1 was positively correlated with MSI in BLCA, CESC, LUAD, LUSC, READ, and SARC, while negatively correlated with MSI in DLBC, but did not show correlation with MSI in other cancers ( Figure 12(e) ).…”
Section: Resultsmentioning
confidence: 99%
“…The SETDB1 expression and HLA-related genes in ACC, CESC, and KIRC were positively correlated but were negatively correlated in other cancers in TCGA ( Figure 12(c) ). TMB and MSI are emerging predictors associated with survival and response to immunotherapy [ 30 , 31 ]. This study showed that SETDB1 was positively correlated with MSI in BLCA, CESC, LUAD, LUSC, READ, and SARC, while negatively correlated with MSI in DLBC, but did not show correlation with MSI in other cancers ( Figure 12(e) ).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study in which the differential functional profiles of MSI colon and endometrial cancers have been assessed using gene expression data. To date, most transcriptomic studies on MSI colon and endometrial cancers have tended to focus on the differentiation of MSI from MSS cancers or on molecular subtyping, [36][37][38][39][40] and we suspect that the lack of research addressing these issues can probably be attributed to the extreme methodological dependence of DEG analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NGS is a more accurate and sensitive method that allows one to analyze various genetic variants in one experimental procedure, eliminating the need to conduct multiple tests in sequence to identify significant biomarkers, thereby significantly reducing the time for selecting therapy. 5 , 197 199 It should be noted that in order to obtain informative results, NGS technologies require a minimum amount of tumor material; they are also able to capture DNA variants present in a minority of cells. 200 To date, many approaches have been proposed for the detection of molecular markers of tumors based on NGS.…”
Section: Experimental Methods For Identification Of Fusion Oncogenesmentioning
confidence: 99%
“… 3 At the nucleotide level, it generates mostly single nucleotide substitutions, short insertions and deletions, insertion of transposable elements, 4 and variability of the microsatellite loci. 5 , 6 In turn, chromosomal instability implies shuffling of the bigger fragments of the genome and is associated with aneuploidy, 7 deletions or amplifications of genes, 8 chromosomal rearrangements, 7 translocations, and gene fusions. 9 Chromosomal instability is currently considered one of the most common features of cancer cells.…”
Section: Genomic Instability and Cancer Evolutionmentioning
confidence: 99%
See 1 more Smart Citation